More answers

The expression 18 plus 6 plus 4b simplifies to 24 + 4b.

Q: 18 plus 6 plus 4b

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The "answer" is the number that ' b ' must be in order to make the statement true.4b + 6 = -2Subtract 6 from each side of the equation:4b = -8Divide each side by 4 :b = -2

15 ac + 20 bc + 6 ad + 8 bd =3a (5c + 2d) + 4b (5c + 2d) =(3a + 4b) (5c + 2d)

29 + - 3 + 6 + - 41 + 18 = 29 - 3 + 6 + 41+ 18 =93

It is a linear expression with one variable, b. Since it is not an equation it cannot be solved.

9x+6 = 7x+18 9x-7x = 18-6 2x = 12 x = 6

Related questions

It is: 4b+6

-2b+8-4b = -5-11b+7 -2b-4b+11b = -5+7-8 5b = -6 b = -6/5

The "answer" is the number that ' b ' must be in order to make the statement true.4b + 6 = -2Subtract 6 from each side of the equation:4b = -8Divide each side by 4 :b = -2

6

15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6

15 ac + 20 bc + 6 ad + 8 bd =3a (5c + 2d) + 4b (5c + 2d) =(3a + 4b) (5c + 2d)

It is: 18+6+6+6+6+9 = 51

6 plus 6 plus 6 is 18. It is the same as 6 x 3 = 18

29 + - 3 + 6 + - 41 + 18 = 29 - 3 + 6 + 41+ 18 =93

It is a linear expression with one variable, b. Since it is not an equation it cannot be solved.

Equality

8/18 plus 1/6 = 11/18